Monitoring infrastructural power: Methodological challenges in studying mobile infrastructures for datafication - Stine Lomborg; Kristian Sick; Sofie Flensburg; Signe Sophus Lai (Internet Policy Review, 2024)
This article discusses how we can locate and understand infrastructural power in mobile infrastructures for datafication through dissecting third-party tracking via so-called software development kits (SDKs). As key material components of mobile infrastructures, SDKs enable app functionality, security, and access to data collection and use by third-party services. However, the methods for investigating SDKs and mobile datafication in general are fragile and in urgent need of development and critical discussion. We explore and discuss methodological pathways for understanding power in the mobile ecosystem. Through exemplifying empirical interventions, derived from a sample of 1129 apps used by 69 Danes participating in the Datafied Living research project, we investigate and discuss how Apple and Alphabet hold infrastructural power and perpetually consolidate their effective mobile duopoly while simultaneously protecting and enhancing their assets in related data markets (e.g. through mobile advertising). We argue that the current infrastructures for mobile datafication impede transparency, systematic democratic monitoring, and ultimately regulation while also limiting the critical capabilities of researchers, as well as open source and hacker environments who must constantly adjust their counter- intelligence measures and tools.
Keywords: 300; Infrastructure; Mobile apps; Software development kit (SDK); Datafication; Infrastructural power